Correlation of Character Values in the Qur'an and Hadith in Hamziyah Ahmad Syauqi Poetry Towards the Ethics of PBA College Students at UIN Walisongo - Iqbal Ahsanul Aula; Fiki Roi’atuz Zibrija; Nazih Sadatul Kahfi (Departement of Mathematics Education, 2024)
This study aims to determine the correlation of character values in the Qur'an and hadith in Hamziyah Ahmad Syauqi on the ethics of PBA UIN Walisongo College Students. The approach used to obtain data is a mix method through the technique of distributing questionnaires, observations and interviews. with the pattern